COLOSTRUM-COLLAGEN-HYDROXYAPATITE COMPOSITE, AN EXCELLENT CANDIDATE BIOMATERIAL FOR BONE REPAIR AND BONE INFECTION MANAGEMENT - Setiawan, Dio Nurdin; Anwar, Mirzaq Hussein; Putri, Kholifatul Wanda; Fiddarain, Nilna Faizah; Widiyanti, Prihartini; Purnobasuki, Heri (Institute of Topical Disease Universitas Airlangga, 2014)
In the case of bone fracture or defect after surgery, which is common in patients with bone cancer (osteosarcoma), it takes a long time for closure and it may cause an infection problem. The use of collagen-hydroxyapatite composite with a blend of colostrum as a scaffold is aimed to accelerate the process of osteoblast growth, inhibite the emergence of infections, and act as bone tissue repair material. The method used was the hydrogel formation process and freeze dry process to remove the solvent and to form pores. The composition of scaffold composite manufactured was 15% collagen, 75% hydroxyapatite and 10% colostrum. Combination of scaffold collagen-hydroxyapatite-colostrum has quite reliable properties because SEM test showed that scaffold could bind to both and could bind to both and could form sufficient pores to provide enough place for bone cells (osteoblats) to grow. The results of MTT assay revealed percentage of above 60%, which indicates that the material is not toxic. In conclusion, collagen-hydroxyapatite-colostrum combination is an excellent biomaterial candidate for bone repair and bone infection management.